Association of PCK1 with Body Mass Index and Other Metabolic Features in Patients With Psychotropic Treatments. Issue 5 (October 2015) - Saigi-Morgui, Núria; Vandenberghe, Frederik; Delacrétaz, Aurélie; Quteineh, Lina; Choong, Eva; Gholamrezaee, Mehdi; Magistretti, Pierre; Aubry, Jean-Michel; von Gunten, MPhil, Armin; Preisig, Martin; Castelao, Enrique; Vollenweider, Peter; et al.
<x xml:space="preserve">Abstract</x> Abstract Weight gain is a major health problem among psychiatric populations. It implicates several receptors and hormones involved in energy balance and metabolism. Phosphoenolpyruvate carboxykinase 1 is a rate-controlling enzyme involved in gluconeogenesis, glyceroneogenesis and cataplerosis and has been related to obesity and diabetes phenotypes in animals and humans. The aim of this study was to investigate the association of phosphoenolpyruvate carboxykinase 1 polymorphisms with metabolic traits in psychiatric patients treated with psychotropic drugs inducing weight gain and in general population samples. One polymorphism (rs11552145G > A) significantly associated with body mass index in the psychiatric discovery sample (n = 478) was replicated in 2 other psychiatric samples (n1 = 168, n2 = 188), with AA-genotype carriers having lower body mass index as compared to G-allele carriers. Stronger associations were found among women younger than 45 years carrying AA-genotype as compared to G-allele carriers (−2.25 kg/m2, n = 151, P = 0.009) and in the discovery sample (−2.20 kg/m2, n = 423, P = 0.0004). In the discovery sample for which metabolic parameters were available, AA-genotype showed lower waist circumference (−6.86 cm, P = 0.008) and triglycerides levels (−5.58 mg/100 mL, P < 0.002) when compared to G-allele carriers. Finally, waist-to-hip ratio was associated with rs6070157 (proxy of rs11552145, r2 = 0.99) in a population-based sample (N = 123, 865, P = 0.022). Our results suggest an association of rs11552145G > A polymorphism with metabolic-related traits, especially in psychiatric populations and in women younger than 45 years.